(untitled) (Raparin Journal of Humanities (RJH), 2025)
Cognitive behavioral therapy it is one of the methods of psychological therapy that massively it was practiced and supported the terms of experience. Awhile the techniques they have roots and roots in the philosophy, Cognitive behavioral therapy a group of assumptions and implications it embodies the philosophical. That is research it follows up for principle and philosophical dimension of Cognitive Behavioral, especially the terms of Cognitive, Behavioral, Socrates dialogue, philosophical Consultation. As well as the terms of stoicisms. After all understand these principles it can richer the clinical practice and the open ways for dialogues between the philosophy and psychological treatment. Cognitive behavioral therapy, combines the cognitive and behavioral approaches for Psychological mental. Which emphasis that is dysfunctional thinking it causes emotional mental and behavioral. Awhile the cognitive behavioral therapy it is managed the terms of experience. It is default assumptions regarding the human cognition and behavior and changes, they are cut of with philosophical questions. this research is investigating at that intersections, in order that light on that is how philosophy as importance subject it advances the cognitive behavioral. Cognitive behavioral therapy is philosophical practical that is on facility assumptions about knowledge and agency and a good life, for this understand the philosophical dimensions of cognitive behavioral treatment it is theoretical participation and it is practical participation it enriches with solutions.